The interactions between autophagy and immune in the liver-adipose-ovary circuit of polycystic ovary syndrome - Nie, Guofeng; Liu, Muxuan; Yang, Luxu; Li, Chanyu; Qu, Chenzhao; Wang, Jing; Mei, Juanjuan; Wang, Yanlin; Han, Lei; Zhang, Xinwei; Wang, Quanmin (Frontiers in Immunology, 2026)
Polycystic ovary syndrome (PCOS) is a common reproductive, endocrine, and metabolic disorder in women of reproductive age, characterized by hyperandrogenemia, insulin resistance, and ovulatory dysfunction. Autophagy, a key cellular homeostasis mechanism, closely interacts with immune-inflammatory responses to drive PCOS pathogenesis. This review highlights the “liver-adipose-ovary circuit”—a pathological network where the liver, adipose tissue, and ovaries crosstalk via autophagy dysregulation, chronic low-grade inflammation, and metabolic disturbances. Abnormal autophagy in adipose tissue induces insulin resistance and inflammatory cytokine release; hepatic autophagy impairment exacerbates non-alcoholic fatty liver disease (NAFLD) and hyperandrogenemia; ovarian autophagy dysfunction disrupts folliculogenesis. These organ-specific abnormalities form a self-reinforcing cycle that amplifies PCOS phenotypes. Clinical therapies targeting this circuit (e.g., quercetin, metformin) show promise by regulating autophagy, improving insulin sensitivity, and restoring reproductive-metabolic balance. Future research should clarify inter-organ molecular mediators and validate autophagy-targeted strategies to advance personalized PCOS treatment.